Perbedaan Rata-Rata Saturasi Oksigen dengan Penggunaan Berbagai Jenis Masker di Era New Normal pada Mahasiswa Prodi Ners Jurusan Keperawatan Tahun Poltekkes Kemenkes Padang 2022 - Roza, Defia; Rangkuti, Adelina Rizki Wardani; Yanti, Nova (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2023)
The new normal means that we wear masks every day. Masks are useful for preventing viruses and bacteria from entering the body. The body inhales oxygen through the nose to deliver it to tissues and cells, while a mask is worn on the face to cover the nose and mouth. Around 43.44% of people are uncomfortable using masks. Based on observations at the Padang Health Polytechnic, there were still students who did not wear masks because they were uncomfortable breathing. Therefore, the aim of this study was to see the difference in oxygen saturation before and after using various types of masks at the Padang Ministry of Health Health Polytechnic. This research is a Quasi Experiment with a One Group Pre-Post Test design. The research was conducted from January to June 2022. The population in this study were students of the Nursing Study Program, Padang Health Polytechnic, with a population of 154 and a sample size of 22 people taken using a purposive sampling technique. The statistical test used is the Wilcoxon signed rank test. The research results showed that the average oxygen saturation before using various types of masks was 97.79 and after 97.18. There was no difference in average oxygen saturation when using cloth masks, surgical masks and KF94 masks. Meanwhile, for KN95 and N95 masks, there is a difference in average oxygen saturation with a p-value of (0.008) and (0.003). The suggestion of this research is that it is recommended for students and the public to continue to use all types of masks according to their daily needs, because the use of masks does not affect oxygen saturation, even though there are masks that change the oxygen saturation value, the oxygen saturation value remains within the range of values. normal.